CSR Communication Model for Sustainable Development Goals through Artificial Intelligence in Indonesia and China - Fajri, Choirul; Fadillah, Dani; Faturrahman, Haris Imam Karim; Chang, Jian; Longani, Kirti Dang (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines how Artificial Intelligence (AI) enhances Corporate Social Responsibility (CSR) communication to advance the Sustainable Development Goals (SDGs) in Indonesia and China. Using a mixed-methods approach, data were collected from 15 in-depth interviews with CSR managers, communication practitioners, and academics, and from a content analysis of 50 corporate CSR reports (25 from Indonesia and 25 from China) published between 2020 and 2024. Quantitative indicators such as the frequency of AI integration in CSR activities and digital engagement rates were coded and compared. Results show that Indonesia emphasizes participatory, multi-platform communication, whereas China adopts a centralized, policy-aligned approach supported by stronger AI infrastructure. AI tools, including chatbots and big-data analytics, improved message precision and stakeholder participation by up to 35% in companies adopting AI-driven CSR strategies. The study proposes an AI-based CSR communication model that links data analytics with stakeholder engagement to increase program transparency and efficiency. These findings contribute empirically to cross-national CSR communication research and provide a practical framework for aligning corporate innovation with sustainable development objectives.